1340. The Burden of Influenza and Rhinovirus Among Hospitalized Adults Post the COVID-19 Pandemic. (4th December 2021) - Reese, Olivia D; Tippett, Ashley; Hussaini, Laila; Salazar, Luis; Taylor, Megan; Ciric, Caroline; Bristow, Laurel; Patel, Vikash; Li, Wensheng; Hsiao, Hui-mien; Stephens, Kathy; Gibson, Theda; et al.
Abstract: Background: Acute respiratory tract infections (ARIs) are a significant cause of morbidity in adults. Influenza is associated with about 490, 600 hospitalizations and 34, 200 deaths in the US in the 2018-2019 season. The burden of rhinovirus among adults hospitalized with ARI is less well known. We compared the burden of influenza and rhinovirus from 2 consecutive winter respiratory viral seasons in hospitalized adults and healthy controls pre-COVID-19 and one season mid-COVID-19 to determine the impact of rhinovirus as a pathogen. Methods: From Oct 2018 to Apr 2021, prospective surveillance of adults ≥50 years old admitted with ARI or COPD/CHF exacerbations at any age was conducted at two Atlanta hospitals. Adults were eligible if they lived within an eight-county region around Atlanta and if their symptom duration was < 14 days. In the seasons from Oct 2018 to Mar 2020, asymptomatic adults ≥50 years old were enrolled as controls. Standard of care test results were included and those enrolled contributed nasopharyngeal swabs that were tested for respiratory pathogens using BioFire® FilmArray® Respiratory Viral Panel (RVP). Results: During the first two seasons, 1566 hospitalized adults were enrolled. Rhinovirus was detected in 7.5% (118) and influenza was detected in 7.7% (121). Rhinovirus was also detected in 2.2% of 466 healthy adult controls while influenza was detected in 0%. During Season 3, the peak of the COVID-19 pandemic, influenza declined to 0% of ARI hospitalizations. Rhinovirus also declined (p=0.01) but still accounted for 5.1% of all ARIs screened (Figure 1). Rhinovirus was detected at a greater rate in Season 3 than in asymptomatic controls in the first 2 seasons (p=0.008). In the first two seasons, Influenza was detected in 8.6% (24/276) of those admitted to the ICU. Rhinovirus was detected in 6.1% (17/276) of those admitted to the ICU but declined to 3.1% (8/258) in Season 3. Figure 1. Percent Positive Cases of Influenza and Rhinovirus between Season 1&2 (hospitalized and healthy controls) vs Season 3 (hospitalized) Conclusion: Dramatic declines occurred in influenza in adults hospitalized with ARI, CHF, or COPD in Atlanta during the COVID-19 pandemic and with enhanced public health measures. Although rhinovirus declined during the COVID-19 pandemic, it continued to be identified at a rate higher than in historical controls. Additional data are needed to understand the role of rhinovirus in adult ARI, CHF, and COPD exacerbations. Disclosures: David L. Swerdlow, MD, Pfizer Vaccines (Employee) Robin Hubler, MS, Pfizer Inc. (Employee) Christina A. Rostad, MD, BioFire Inc, GSK, MedImmune, Micron, Janssen, Merck, Moderna, Novavax, PaxVax, Pfizer, Regeneron, Sanofi-Pasteur. (Grant/Research Support, Scientific Research Study Investigator, Research Grant or Support)Meissa Vaccines (Other Financial or Material Support, Co-inventor of patented RSV vaccine technology unrelated to this manuscript, which has been licensed to Meissa Vaccines, Inc.) Larry Anderson, MD, ADVI (Consultant)Bavarian Nordic (Consultant)Novavax (Consultant)Phizer (Grant/Research Support, Scientific Research Study Investigator)Sciogen (Research Grant or Support) Nadine Rouphael, MD, pfizer, sanofi, lily, quidel, merck (Grant/Research Support) Nadine Rouphael, MD, Lilly (Individual(s) Involved: Self): Emory Study PI, Grant/Research Support; Merck (Individual(s) Involved: Self): Emory study PI, Grant/Research Support; Pfizer: I conduct as co-PI the RSV PFIZER study at Emory, Research Grant; Pfizer (Individual(s) Involved: Self): Grant/Research Support, I conduct as co-PI the RSV PFIZER study at Emory; Quidel (Individual(s) Involved: Self): Emory Study PI, Grant/Research Support; Sanofi Pasteur (Individual(s) Involved: Self): Chair phase 3 COVID vaccine, Grant/Research Support Evan J. Anderson, MD, GSK (Scientific Research Study Investigator)Janssen (Consultant, Scientific Research Study Investigator, Advisor or Review Panel member)Kentucky Bioprocessing, Inc (Advisor or Review Panel member)MedImmune (Scientific Research Study Investigator)Medscape (Consultant)Merck (Scientific Research Study Investigator)Micron (Scientific Research Study Investigator)PaxVax (Scientific Research Study Investigator)Pfizer (Consultant, Grant/Research Support, Scientific Research Study Investigator)Regeneron (Scientific Research Study Investigator)Sanofi Pasteur (Consultant, Scientific Research Study Investigator)